PEMBERDAYAAN EKONOMI MASYARAKAT DI DESA CIKOLELET MELALUI KELOMPOK TANI MEKAR BAKTI 1 - Irwan Zulkarnain Trisnamansyah; Andriyanto Andriyanto; Nurkholifah Nurkholifah; Sopi Nurhikmah; Ulhani Ulhani (Pusat Pengabdian Kepada Masyarakat Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Empowerment is an attempt to help people to help themselves or an attempt to lead people to learn to lead themselves. This study aims to find out how the economic empowerment of the community is carried out in Cikolelet Village through the Mekar Bakti 1 Farmer Group and also the things that are supporting and inhibiting factors in these empowerment activities. The method used in this research is descriptive qualitative method in which the researcher will describe or explain the problems studied in accordance with the facts in the field. Through the social welfare science approach, it is shown that community empowerment in rural communities is considered quite effective in improving health. Based on the research results, it is known that the empowerment carried out by farmer groups is through soybean seed cultivation, tofu making, goat milk management, and mallet (cikolelet honey). In addition, it is also known that the supporting fact is that the community in Cikolelet Village actively participates in all empowerment activities. However, the place and marketing access have not been fully supported.